A comparative analysis of COVID-19 cases with comorbidities according to epidemiological and demographic characteristics in South Bengkulu Regency, Indonesia - Diniarti, Fiya; Pratiwi, Bintang Agustina; Surahman, Fery; Rohani, Tuti (Public Health of Indonesia, 2022)
Background: COVID-19 continues to be a global threat. Indonesia has the highest COVID-19 in ASEAN. Objective: This study aimed to analyze COVID-19 cases according to epidemiological and demographic characteristics in South Bengkulu Regency, Indonesia. Methods: This research used quantitative methods with a case-control approach. A sample of 326 people was included as secondary data obtained from the Regional General Hospital of South Bengkulu Regency, Indonesia. The sampling technique uses consecutive sampling. Data (age, gender, education) from medical records in hospitals and epidemiological data (contact records with patients, travel records, and social contact records) were measured using questionnaires validated online (Google form). Chi-square and multiple regression logistics were used for data analysis. Result: Most groups infected with COVID-19 were in the risk age range (46.6%), men (51.2%), low education (48.2%), had a record of contact with patients (54.6%), had a travel record (53.7%), had a record of social contact (51.5%) and had the highest comorbidities such as tuberculosis (36.2%). There were significant relationships between age (p = 0.004), sex (p = 0.002, OR= 2.054), history of contact with the patient (p = 0.001, OR= 2.120), travel history (p = 0.003, OR= 1.959), social contact history (p = 0.003, OR = 2.003), and comorbidities type (p = 0.017) with the incidence of COVID-19. The dominant factor associated with COVID-19 was the record of social contact (p = 0.032, OR = 1.724). Conclusion: The study findings can be used to increase public knowledge about COVID-19 prevention and mitigation efforts as one of the strategies to reduce the risk of COVID-19 events.